PENGGUNAAN MEDIA PEMBELAJARAN ASSEMBLR EDU PADA MATA PELAJARAN IPS TERHADAP MINAT BELAJAR SISWA KELAS VIII - A. Nur Putri; Firdaus R; Kasman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The use of media is still menoton only using learning media such as whiteboards and printed books will certainly hinder the learning process, so new innovations are needed in the teaching and learning process that are interesting and fun so that students become more interested in participating in learning by using Assemblr Edu learning media. The purpose of this study was to determine the effect of using Assemblr Edu learning media in social studies subjects on the learning interest of class VIII students of SMP Negeri 2 Sungguminasa, Gowa Regency. The type of research used in this study is a type of quantitative research with experimental methods. Based on the calculations carried out, it was obtained tCount = 6.578. The table price with a significant level = 0.05 and degrees of freedom (dk) = 184 from the distribution table 1.653 with the results of the calculation of t Count> from t Table or, 6.578> 1.653 thus H₁ is accepted and H₀ is rejected. This shows that there is an effect of Asemblr Edu learning media on student interest in social studies class VIII at SMP Negeri 2 Sungguminasa.